2016
DOI: 10.1111/jar.12245
|View full text |Cite
|
Sign up to set email alerts
|

Facing the Unknown: Intolerance of Uncertainty in Children with Autism Spectrum Disorder

Abstract: Participants were able to identify and provide examples of IU suggesting that it is a recognizable construct among children with ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 36 publications
5
29
0
2
Order By: Relevance
“…Hodgson et al (2016) conducted focus groups of nine parents of ASD children without intellectual disabilities. The parents easily differentiated IU from a general dislike of change, including discomfort with unknown situations such as delayed flights on a planned trip; and discomfort with uncertainty even in known situations, when a child moves to middle school and is required to use a pen instead of a pencil but is afraid she might make a mistake and not be able to erase it.…”
Section: Intolerance Of Uncertainty In Asdmentioning
confidence: 99%
“…Hodgson et al (2016) conducted focus groups of nine parents of ASD children without intellectual disabilities. The parents easily differentiated IU from a general dislike of change, including discomfort with unknown situations such as delayed flights on a planned trip; and discomfort with uncertainty even in known situations, when a child moves to middle school and is required to use a pen instead of a pencil but is afraid she might make a mistake and not be able to erase it.…”
Section: Intolerance Of Uncertainty In Asdmentioning
confidence: 99%
“…Using factor analytic techniques, the study identified four valid anxiety subscales, including an uncertainty scale. Hodgsonet al ( 2017 ) undertook focus groups with parents of autistic young people exploring the concept of IU. Parents differentiated IU from dislike of change and from fear, discussed examples of IU and its impact on their children, and suggested that IU is a recognisable and important construct associated with anxiety that is distinguishable from but related to features of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Given evidence of an association between IU and anxiety in the typically developing population, researchers have been investigating this association in young people with ASD. IU has been found to be a recognisable construct in children with ASD, as identified by parents (Hodgson, Freeston, Honey & Rodgers, 2016). Evidence suggests that it may act as a mediator between ASD symptoms and anxiety with higher levels of IU in ASD accounting for the greater rates of anxiety associated with the disorder (Boulter, Freeston, South & Rodgers., 2014).…”
mentioning
confidence: 99%